1987
DOI: 10.1128/mcb.7.2.622
|View full text |Cite
|
Sign up to set email alerts
|

Induction of urokinase-type plasminogen activator by UV light in human fetal fibroblasts is mediated through a UV-induced secreted protein.

Abstract: Plasminogen activator was previously shown to be induced by UV light in human cells with low capacity to repair UV-induced DNA lesions. We now show that in human fetal fibroblasts UV light enhanced the two mRNA species coding for the urokinase-type plasminogen activator (uPA) and the tissue-type plasminogen activator, but immunological analysis revealed exclusively uPA activity. Several independent and complementary experiments indicated that induction of uPA was mediated, apparently entirely, through a UV-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 61 publications
1
31
1
Order By: Relevance
“…Moreover, a UV-induced secreted factor was proposed to mediate uPA induction in low-repair-capacity human fetal fibroblasts (72,74). These reports, however, contrast with previously mentioned findings showing that UV activates cytoplasmic kinases through pathways used by growth factors, independently of UV-induced DNA damage (26,27,77).…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Moreover, a UV-induced secreted factor was proposed to mediate uPA induction in low-repair-capacity human fetal fibroblasts (72,74). These reports, however, contrast with previously mentioned findings showing that UV activates cytoplasmic kinases through pathways used by growth factors, independently of UV-induced DNA damage (26,27,77).…”
contrasting
confidence: 54%
“…5 and 6), suggesting that the uPA gene could be activated, at least in part, by a cytoplasm-transduced signal. These results have to be reconciled with studies showing that UV caused a late (occurring a few days postirradiation) induction of human uPA expression in normal and xeroderma pigmentosum cells after inducing a signal originating from DNA damage (64,74). At present, we can only speculate on these apparently different origins of UV induction.…”
Section: Discussionmentioning
confidence: 49%
“…We favour U.V.-induced synthesis and secretion of several growth factors (Schorpp et al, 1984;Rotem et al, 1987;Stein et al, 1989a;Yarosh et al, 1993) and their autocrine action as cause of the delayed response. The delay depends on the time required to reach a threshold level in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The constitutive EPR in this mutant, however, is the same as in wild-type cells. It has been shown that mammalian cells synthesize a novel class of secretory protein in response to UV damages that effectively transmit UV-specific messages between cells [25,26]. As also seen in frog cells, regulation of EPR is mediated by (a) new protein(s).…”
Section: Discussionmentioning
confidence: 96%